2003
DOI: 10.1111/j.1750-3639.2003.tb00474.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequent LOH at Chromosome 12q22‐23 and Apaf‐1 Inactivation in Glioblastoma

Abstract: Glioblastoma (GB) often has loss of heterozygosity on the chromosomes, 1p, 10p, 10q, 11p, 17p, 19q, 22q, and several others. In the case of chromosome 12q; however, it remains to be seen whether LOH occurs. Apaf‐1, the apoptotic protease activating factor‐1, located at chromosome 12q22‐23, is a major effecter of the p53 mediated apoptosis pathway, and Apaf‐1 inactivation due to chromosome 12q22‐23 LOH and hypermethylation may be involved in some of the neoplasms in malignancy. However, little is known about th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Aberrant expression of Apaf-1 with defects in dATP-mediated caspase-3 activation is also detected in male germ cell tumors (7). Recently, Watanabe et al (8) reported frequent inactivation of Apaf-1 due to loss of heterozygosity in glioblastoma. Furthermore, a frame-shift mutation of the mononucleotide tract in the Apaf-1 gene is associated with gastrointestinal cancer of the microsatellite mutator phenotype (9).…”
Section: Introductionmentioning
confidence: 98%
“…Aberrant expression of Apaf-1 with defects in dATP-mediated caspase-3 activation is also detected in male germ cell tumors (7). Recently, Watanabe et al (8) reported frequent inactivation of Apaf-1 due to loss of heterozygosity in glioblastoma. Furthermore, a frame-shift mutation of the mononucleotide tract in the Apaf-1 gene is associated with gastrointestinal cancer of the microsatellite mutator phenotype (9).…”
Section: Introductionmentioning
confidence: 98%
“…16 Alternatively, the mechanisms repressing Apaf-1 in primary tumor specimens can be occasionally altered through genetic or epigenetic changes that accompany passaging in culture (e.g., by potentiation of the Rb/E2F-1 pathway, which can control Apaf-1 mRNA levels 17 ). The fact that certain leukemia cells 18,19 as well as AML, ALL, and CML blasts 18 and cells from glioblastoma 20 and cervical cancer 21 may also inactivate Apaf-1 expression, in part by methylation, suggests a broader impact of tumorrelated events modulating Apaf-1 expression.…”
mentioning
confidence: 99%
“…6 In this regard, the two proteins seem to act as tumor suppressors. In fact, the APAF1 gene does not appear to be functional in melanoma, 7-9 glioblastoma, 10,11 gastrointestinal tumor, 12 germ line tumor. 13 More recently, a poor prognosis was observed in patients suffering from B-type chronic lymphocytic leukemia with loss of APAF1 expression and additional p53 mutation.…”
Section: Introductionmentioning
confidence: 99%